2022
DOI: 10.6026/97320630018450
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activity of a nanoparticle based intracanal drugs

Abstract: The most common intracanal medication is calcium hydroxide. Its efficacy can be affected by a number of factors, including pH, serum proteins, collagen, and dentin. It's also ineffective against E. faecalis and fungus, lacks an anti-inflammatory component, and has mixed reviews when it comes to pain relief. Natural alternatives to synthetic intracanal medication are being researched at the moment. We evaluated the antioxidant and anti-inflammatory activity of green synthesized silver nanoparticle based intraca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Our study showed 80% of maximum anti-inflammatory activity at 80 µg/mL compared to the standard, when compared to the other study of TiO 2 -ZnO NC exhibited 83% of activity at 80 µg/mL concentration [35] which is similar to our study. This helps to understand the activity of titanium nanoparticles.…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed 80% of maximum anti-inflammatory activity at 80 µg/mL compared to the standard, when compared to the other study of TiO 2 -ZnO NC exhibited 83% of activity at 80 µg/mL concentration [35] which is similar to our study. This helps to understand the activity of titanium nanoparticles.…”
Section: Discussionsupporting
confidence: 90%
“…This result suggests that the green synthesized Zn-TiO2 NC effectively acts against oral pathogens such as S. mitis and S. mutans . [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study demonstrate that biosynthesized CaCO 3 derived from a 77% methanol extract of bark exhibits notably higher total antioxidant capacity in comparison to NPs produced from aqueous (74%) and ethanol (70%) extracts. This implies that CaCO 3 synthesized using methanol is particularly effective at scavenging free radicals, while those produced with acetone display a comparatively reduced capacity to neutralize free radicals ( Nasim, 2022 ). The nanoparticle-based treatments exhibited substantial inhibitory effects, with percentages of inhibition recorded at 75%, 81%, and 63%.…”
Section: Discussionmentioning
confidence: 99%